Psychology - Wortman, Camille B; Loftus, Elizabeth F; Marshall, Mary (Alfred A. Knopf, 1988)
In this revised introductory psychology text, the authors aim to teach students the \"how\" and \"why\" of what psychologists do in their research, integrating a serious critical thinking approach into the research-oriented text.
Keywords: psychologie; Psychology; psychologie, klinická psychologie